SWOT ANALYSIS AT PT. PEGADAIAN (PERSERO) BRANCH OF WIYUNG SURABAYA - Rendy Suciana; Elok Damayanti (Jurnal Ekonomi, 2020)
This study aims to explore PT Pegadaian (Persero) Branch Wiyung Surabaya using qualitative research methods. The development at PT Pegadaian is increasingly progressing, but this should not make it less competitive with other competitors. Many things must be addressed at PT Pegadaian, one of which is by providing and providing the best quality service to its customers, therefore it requires strategic management to compete with other pawning services. So to determine the strategy used, the researcher uses a SWOT analysis, namely the steps through a matrix approach, identification of the external and internal environment, EFAS and IFAS analysis, determining the score so that the formulation of the competitive strategy will be found. The results of the SWOT analysis will find strengths, weaknesses, opportunities, and threats to PT Pegadaian (Persero) Surabaya.